A dual role for cell plate‐associated PI4Kβ in endocytosis and phragmoplast dynamics during plant somatic cytokinesis. (7th January 2019) - Lin, Feng; Krishnamoorthy, Praveen; Schubert, Veit; Hause, Gerd; Heilmann, Mareike; Heilmann, Ingo
Abstract: Plant cytokinesis involves membrane trafficking and cytoskeletal rearrangements. Here, we report that the phosphoinositide kinases PI4Kβ1 and PI4Kβ2 integrate these processes in Arabidopsis thaliana ( Arabidopsis ) roots. Cytokinetic defects of an Arabidopsis pi4kβ1 pi4kβ2 double mutant are accompanied by defects in membrane trafficking. Specifically, we show that trafficking of the proteins KNOLLE and PIN2 at the cell plate, clathrin recruitment, and endocytosis is impaired in pi4kβ1 pi4kβ2 double mutants, accompanied by unfused vesicles at the nascent cell plate and around cell wall stubs. Interestingly, pi4kβ1 pi4kβ2 plants also display ectopic overstabilization of phragmoplast microtubules, which guide membrane trafficking at the cell plate. The overstabilization of phragmoplasts in the double mutant coincides with mislocalization of the microtubule‐associated protein 65‐3 (MAP65‐3), which cross‐links microtubules and is a downstream target for inhibition by the MAP kinase MPK4. Based on similar cytokinetic defects of the pi4kβ1 pi4kβ2 and mpk4‐2 mutants and genetic and physical interaction of PI4Kβ1 and MPK4, we propose that PI4Kβ and MPK4 influence localization and activity of MAP65‐3, respectively, acting synergistically to control phragmoplast dynamics. Synopsis: Phosphoinositides coordinate a host of processes and signalling cascades in eukaryotic cells, but little is known about how they regulate cytokinesis in plants. Phosphatidylinositol 4‐kinases PI4Kβ1 and PI4Kβ2 control membrane trafficking and microtubule dynamics in Arabidopsis thaliana root by interacting with cell plate‐associated MPK4 and regulating proper localization of microtubule binding protein PLEIADE/MAP65‐3. PI4Kβ1 localizes at the leading edge of growing cell plates in cytokinetic Arabidopsis root cells. pi4kβ1 pi4kβ2 double mutant plants display overstabilized phragmoplast microtubules in the central zone of the cell plate, and reduced endocytosis during cytokinesis. Microtubule‐associated protein MAP65‐3 mislocalizes in cytokinetic cells in pi4kβ1 pi4kβ2 double mutants. MPK4, an upstream regulator of MAP65‐3, interacts genetically and physically with PI4Kβ1 to control microtubule stability. PI4Kβ1 and PI4Kβ2 regulate microtubule dynamics in Arabidopsis in both cytokinetic and interphase root cells. Abstract : Phosphatidylinositol 4‐kinases PI4Kβ1 and PI4Kβ2 control membrane trafficking and microtubule dynamics in Arabidopsis thaliana roots by interacting with cell plate‐associated MPK4 and regulating proper localization of microtubule binding protein PLEIADE/MAP65‐3.